Evaluation of cholesterol transformation abilities and probiotic properties of Bacteroides dorei YGMCC0564 - He, Zhili; Wang, Tinghui; Zhang, Shichang; Shi, Kuojiang; Wang, Fan; Li, Yanzhao; Lin, Chanqing; Chen, Jianguo (Frontiers in microbiology, 2023)
Hypercholesterolemia, a risk factor for cardiovascular disease (CVD), often requires therapeutic agents with varying degrees of side effects. This has created a need for safe and natural alternatives such as medications or functional foods that can improve lipid metabolism and reduce cholesterol levels. In recent years, Next-generation probiotics (NGPs) have recently emerged as a potential solution, offering distinct mechanisms compared to traditional probiotics. Among the NGPs, Bacteroides , a dominant bacterial genus in the human gut, has gained significant attention due to its prevalence, ability to break down plant polysaccharides, and production of short-chain fatty acids (SCFAs). Recent evidence has demonstrated that Bacteroides effectively reduces cholesterol levels, prevents obesity, and lowers the risk of CVD. However, research on Bacteroides is currently limited to a few species, leaving rooms for exploration of the beneficial functions of different species in this genus. In this study, we isolated 66 Bacteroides strains, including 9 distinct species, from healthy adults’ fecal samples. By comparing their ability to assimilate cholesterol, we found that the transformation ability was not specific to any particular species. Notably, Bacteroides dorei YGMCC0564 revealed superior cholesterol-lowering capabilities and bile salt hydrolase (BSH) activity in vitro , surpassing that of Lactobacillus GG (LGG). YGMCC0564 exhibited favorable probiotic characteristics, including high survival rate in vitro simulation of gastrointestinal digestion, excellent adhesion ability, susceptibility to antibiotics, absence of hemolysis or virulence genes, and substantial production of SCFAs. The strain also demonstrated remarkable bile salt deconjugation activities and upregulation of the BT_416 gene associated with cholesterol, providing insights into a possible molecular mechanism underlying its cholesterol-reducing activity. These findings establish YGMCC0564 as a promising NPG candidate for improving cardiovascular health.